Proces formowania się państwa Piastów - Kóčka-Krenz, Hanna (Folia Praehistorica Posnaniensia, 2015)
The paper presents a question of the Piast state formation based on the changes in the network of settlements, in particular the strongholds. The results of archaeological research, enriched by studies performed by historians, show that the processes of forming the Piast state took a relatively short time and it did not entail a period of competition between local tribal leaders. Its character was revolutionary, which determines the uniqueness of the processes occurring in the Polish lands over a thousand years ago.